2009
DOI: 10.1097/scs.0b013e3181bec6d5
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Mandibular Fracture Accompanying a Gunshot Wound

Abstract: Gunshot injuries of the mandible can result in high rates of complications, especially in cases of bone loss. A fractured mandible accompanying a gunshot wound almost always has an external wound; the fracture is always compound and comminuted. Sometimes management of these injuries may require multiple surgical interventions. In this clinical report, treatment of a patient, who had a mandibular fracture due to a gunshot wound, is presented.A 52-year-old man with a mandibular fracture in the right mandibular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…In this study, mean values of LP thickness surrounding the most lingual root were considerably 'thin' (0.89 mm), according to Toltsunov L.'s suggestion 11 . The measured bone thickness was comparable of reported values from other studies which are ranging from 0.65 to 1.25 mm [9][10][11] . Additionally, the result revealed that among three examined positions, the most lingual position was noted at apical third which is in line with the result of Emes et al 9 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, mean values of LP thickness surrounding the most lingual root were considerably 'thin' (0.89 mm), according to Toltsunov L.'s suggestion 11 . The measured bone thickness was comparable of reported values from other studies which are ranging from 0.65 to 1.25 mm [9][10][11] . Additionally, the result revealed that among three examined positions, the most lingual position was noted at apical third which is in line with the result of Emes et al 9 .…”
Section: Discussionsupporting
confidence: 88%
“…The measured bone thickness was comparable of reported values from other studies which are ranging from 0.65 to 1.25 mm [9][10][11] . Additionally, the result revealed that among three examined positions, the most lingual position was noted at apical third which is in line with the result of Emes et al 9 . In other words, the morphology of LP surrounding MTM in Vietnamese population is similar to other ethnics and bone thickness is considerably thin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They are uncommon and typically seen in the setting of comminuted or multiple fractures (69,83). Osteomyelitis and nonunion (in the mandible, more than 8 weeks of delayed healing [84]) often occur together and account for most cases of complications. These inflammatory complications are greatly influenced by patient factors, including drug and alcohol abuse, noncompliance, poor dental hygiene, systemic disease including diabetes and human immunodeficiency virus, and advanced age (5,28).…”
Section: Major and Minor Complicationsmentioning
confidence: 99%
“…It is important to establish the CT features of postoperative inflammatory complications, regardless of whether the complication is major or minor. Irregular resorbed bone with mottled or rounded sclerotic fracture edges (84), loose screws, sequestration of devitalized comminuted fragments, persistent fracture line, and/or step-off strongly suggests the presence of osteomyelitis (43,83) (Fig 25). During repeat surgery, the placement of reconstruction plate screws or external fixation pins within 10 mm of infected bone should be avoided because of the decreased mineral content near the bone ends (43).…”
Section: Major and Minor Complicationsmentioning
confidence: 99%